Fraud pentagon theory in detecting financial perception of financial reporting with good corporate governance as moderator variable - Sawaka K., I Gusti Ngurah Hiwa; Ramantha, I Wayan (International research journal of management, IT and social sciences, 2020)
This study aims to provide empirical evidence about fraud pentagon theory in detecting perceptions of fraud with good corporate governance as moderating. The study was conducted at all PT BPRs in Bali Province who held positions as directors and commissioners. The sampling technique uses saturated samples and uses the Yamane formula and produces 225 samples that are worthy of study. The data analysis technique used in moderated regression analysis. The test results found that the pentagon theory fraud indicator namely pressure negatively affects the perception of fraudulent financial reporting. Opportunities and rationality have a positive effect on perceptions of financial reporting fraud. Competence and arrogance do not affect the perception of financial reporting fraud. GCG weakens the negative effect of pressure on perceptions of fraudulent financial reporting. GCG weakens the positive influence of opportunity and rationality on the perception of fraud. GCG does not moderate the effect of competence and arrogance on perceptions of fraudulent financial reporting, but GCG is a type of potential moderation for the interaction of competence and arrogance.